2007
DOI: 10.1016/j.tripleo.2007.01.027
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriologic investigation of the effects of sodium hypochlorite and chlorhexidine during the endodontic treatment of teeth with apical periodontitis

Abstract: Objective. This clinical study was undertaken to compare the effectiveness of 2.5% sodium hypochlorite (NaOCl) and 0.12% chlorhexidine digluconate as irrigants in reducing the cultivable bacterial populations in infected root canals of teeth with apical periodontitis. Study design. According to stringent inclusion/exclusion criteria, 32 teeth with primary intraradicular infections and chronic apical periodontitis were selected and followed in the study. Bacterial samples were taken at the baseline (S1) and aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
97
2
14

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 146 publications
(127 citation statements)
references
References 64 publications
14
97
2
14
Order By: Relevance
“…This finding is consistent with the results of other investigators, who showed no differences in bactericidal efficacy between NaOCl and CHX 10,[39][40][41][42] . CTR is a cationic detergent that has an antibacterial activity against many gram-positive and gram-negative bacteria 41) .…”
Section: Discussionsupporting
confidence: 93%
“…This finding is consistent with the results of other investigators, who showed no differences in bactericidal efficacy between NaOCl and CHX 10,[39][40][41][42] . CTR is a cationic detergent that has an antibacterial activity against many gram-positive and gram-negative bacteria 41) .…”
Section: Discussionsupporting
confidence: 93%
“…Chlorhexidine (CHX) has been recommended as an alternative to NaOCl during root canal preparation, especially in cases of open apex, root resorption, foramen enlargement and root perforation, due to its biocompatibility, or in cases of allergy related to bleaching solutions 9 . Clinical investigations have reported that CHX and NaOCl have comparable effects in eliminating bacteria [10][11] . However, only CHX has a property known as substantivity -capacity to adsorb to surfaces and maintain a prolonged antimicrobial activity 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Streptococcus species have commonly been detected in samples taken immediately after endodontic treatment procedures (3,4,18,19,21,28) and in root canal-treated teeth undergoing retreatment (6,8,11,12,26,30). This suggests that these bacteria may be involved with persistent infections that result in persistent disease.…”
mentioning
confidence: 99%